Somatic hybridization between ’Rangpur’ lime and ’Cleópatra’ mandarin - Latado, Rodrigo Rocha; Derbyshire, Maria Teresa Vitral de Carvalho; Tsai, Siu Mui; Neto, Augusto Tulmann (Pesquisa Agropecuaria Brasileira, 2002)
The aim of this work was to obtain somatic hybrids between ’Rangpur’ lime (Citrus limonia Osbeck) and ’Cleópatra’ mandarin (Citrus reshni Hort.), to be used as a citrus rootstock. ’Rangpur’ lime is the most important Brazilian citrus rootstock due to its higher horticultural performance. Nevertheless, this species is susceptible to blight disease, which is responsible for the death of millions of productive trees per year in Brazil. ’Cleópatra’ mandarin has become an increasingly important rootstock in other countries and has been reported as being tolerant to citrus blight disease. Leaf protoplasts and protoplasts from embryogenic cell suspension cultures were fused using PEG solution (50%) and further cultivation in agarose. The frequency of heterokaryon formation was 5.1% to 6.8%. More than 500 plants were regenerated from these fusion experiments and 180 were tested. Among them, 11 plants were confirmed to be a somatic hybrid by means of molecular markers (RAPD) and isoenzymes markers (PO, IDH and PGI systems). Six plants were acclimatized, planted in the soil and have been multiplied by cuttings in order to evaluate their potential as citrus rootstocks.